(untitled) (Ekonomski vjesnik/Econviews - Review of Contemporary Business, Entrepreneurship and Economic Issues, 2018)
The authors explore the specifics of the socio-cultural contribution of migrants to the Croatian and German economies. The paper looks into the theoretical background of migrant contributions to entrepreneurship by reviewing, comparing and analysing secondary data on the current situation in German and Croatian entrepreneurship with the emphasis on employment and self-employment of migrants and the contribution of their distinct cultures to the economies of the two countries. This is accompanied by some concrete examples of successful or unsuccessful internationalization, multiculturalism of societies, and overcoming cultural challenges in both economies. If we accept that each culture is a "world for itself", because of its specific features there is no universal model of business behaviour. Every culture must be investigated separately. Is this the case in Croatia?